PLAY AS AFACTOROF SOCIALISATION IN THE CHILDHOOD - Aramavičiūtė, Vanda; Jasiūnaitė, Placida (Acta Paedagogica Vilnensia, 2011)
The article actualises the importance of socialisation nurturing a full-fledged personality. Acknowledging the meaning and particularity of socialisation in ontogenesis, the particular importance of primary socialisation in the childhood is pointed out. Play stands out as one of the factors that determine socialisation processes in current world. On the basis of the play theories of the 19th and 20th centuries (personality, satisfaction, functional satisfaction, surplus of powers, compensation, transitional objects, exercises or self-education, self-expression, transactional analysis) and data of contemporary researches, play is defined as the main child’s activity: free, personal, interpersonal, creative, therapeutic, special, preparatory, etc. Having discussed the purpose and meaning of play as expressions of play functions from the holistic point of view, the varied influence of play on child’s socialisation is revealed. Evaluating this effect from the point of view of child’s social self-development, it is stated that through naturally occurring situations during play, a child is exposed to real possibilities to learn to perform various social roles, to try out new model of behaviour and communication that help him/her to better adjust to their peers, to involve into group’s life and to achieve a favourable status. In terms of child’s individuality development a child is able to acquire new abilities, skills, indivual experience, norms and regulations, to experience joy and pleasures. Generalising, play may lay valuable foundation for development of child’s social and individual personality, which allows for considering play as a significant factor of socialisation in the childhood.